Model Nilai Tambah Produk Pertanian Gambir (Kasus: Petani Gambir Kecamatan Iv Jurai Kabupaten Pesisir Selatan) - Hasdi Aimon; Elida Elida; Zul Azhar (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
Abstract: The study aims to explain the added value, cost, and revenues of gambir farmers in order to improve the welfare of farmers. It’s uses primary data and makes farmers of gambir as a source of information related to concepts in research. The analysis model uses the production model, cost model, revenue model, and economic profit model. The results showed that the production of gambir not yet optimal (constant return to scale) and production cost has been efficient if gambir leaves input used 245 sack and composite input 145 unit so the gambir production 195 kg. than economically farmers have profitable if price optimism scenario. Accordingly, this study recommends to the policy makers in order to provide guidance to the gambir farmers to not only produce gambir but also other derivative products that are economically profitable and welfare farmers of gambir.